Correlation of Blood Creatinine Levels with The Result of Urine Sediment Analysis in Chronic Kidney Failure Patient - Siti Zaetun; Rohmi Rohmi; Andi Dwi Oktaviani; Lalu Srigede (Poltekkes Kemenkes Mataram, 2024)
Chronic Kidney Failure is a condition caused by a gradual and chronic decline in kidney function. This situation can affect to creatinine levels. Creatinine is the result of endogenous metabolism that is useful for assessing glomerular function, in the event of renal dysfunction then the filtration ability of creatinine will be reduced and serum creatinine will increase. Urine sediment is produced from the results of urine concentration consisting of calcium salts. This concentrated urine comes from the kidneys with a variety of causes, one of which is chronic kidney failure, flows through the ureter to the bladder and continues to the urethra until the urethral. Objective: To find out the correlation of blood creatinine levels with the results of urine sediment analysis in patients with chronic kidney failure. Method: This research is observational analytical with a cross sectional approach to determine the correlation between independent and dependent variables. The sample is taken purposive sampling by selecting a sample based on certain criteria. The collected data is then analyzed using Spearman statistical tests. Results: Examination of creatinine levels in chronic kidney failure patients obtained 6.67 mg/dl. The average urine sediment found erythrocytes as many 2-3/HPF to many/HPF. Conclusion: There is a correlation of blood creatinine levels with the results of urine sediment analysis in patients with chronic kidney failure.